2016
DOI: 10.1093/ntr/ntw389
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Graphic Warning Labels Are Not Created Equal: They Can Increase or Decrease Smokers’ Quit Intentions Relative to Text-only Warnings

Abstract: This research is the first to directly manipulate two emotion levels in sets of nine cigarette graphic warning images and compare them with text-only warnings. Among adult and teen smokers, high-emotion graphic warnings were associated with increased risk perceptions and quit intentions versus text-only warnings. Low-emotion graphic warnings backfired and tended to reduce risk perceptions and quit intentions versus text-only warnings. Policy makers should be aware that merely placing images on cigarette packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 32 publications
6
60
1
Order By: Relevance
“…First, it indicates that arousal is an important emotional dimension for the perceived effectiveness of the warning labels. This result is in line with prior studies (Evans et al, 2017;Noar et al, 2016) and with the recent findings from Bekalu et al (2018) who concluded that beyond valence, arousal seems to be a strong factor to consider in labelling tobacco products. To make an evaluative judgment, people often rely on the intensity of their feelings and then use those feelings as an indicator of their judgment.…”
Section: Discussionsupporting
confidence: 92%
“…First, it indicates that arousal is an important emotional dimension for the perceived effectiveness of the warning labels. This result is in line with prior studies (Evans et al, 2017;Noar et al, 2016) and with the recent findings from Bekalu et al (2018) who concluded that beyond valence, arousal seems to be a strong factor to consider in labelling tobacco products. To make an evaluative judgment, people often rely on the intensity of their feelings and then use those feelings as an indicator of their judgment.…”
Section: Discussionsupporting
confidence: 92%
“…This allows cigarette stick warnings the potential to be as effective or more effective than current packaging warnings in reducing tobacco use . However, similar to graphic images on cigarette packaging, cigarette stick warnings would need to evoke a significant emotional response and ensure accurate perceptions of risk and increased quit intentions . Many pharmacists in the survey and interviews cited the health warnings on cigarette sticks as being ‘in your face’ and likely to attract the attention of the smoker and onlookers.…”
Section: Discussionmentioning
confidence: 99%
“…[14,17,37] However, similar to graphic images on cigarette packaging, cigarette stick warnings would need to evoke a significant emotional response and ensure accurate perceptions of risk and increased quit intentions. [38] Many pharmacists in the survey and interviews cited the health warnings on cigarette sticks as being 'in your face' and likely to attract the attention of the smoker and onlookers. However, including health warnings on cigarette sticks would likely be resisted by tobacco manufacturers, as has been the case for tobacco packaging warnings and plain packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that highly severe HWLs increase smokers' intention to quit smoking as compared with less severe HWLs [5] and are more believable than symbolic warnings [6]. Furthermore, high emotion HWLs have been shown to elicit greater emotional reaction than lower-emotion HWLs, with emotional reaction to HWLs related to higher risk perceptions of smoking [7]. In contrast, other research on a range of different health outcomes indicates that highly severe warnings may result in defensive reactions [8][9][10].…”
Section: Introductionmentioning
confidence: 98%